Brookings Papers on Economic Activity / Microeconomics 1995 - Baily Martin Neil; Reiss Peter C; Winston Clifford (Brookings Institution, 1995)
Old Dogs and New Tricks: Determinants of the Adoption of Productivity-Enhancing Work Practices, Exporters and Jobs and Wages in U.S. Manufacturing: 1967-1987, Participation and Productivity: A comparison of worker Cooperatives and Conventional Firms in the Plywood Industry, The Information-Intergrated Channel: A Study of the U.S. Apparel Industry, A Bayesian Learning Model Fitted to a Variety of Empirical Learning Curves, Efficiency in Manufacturing and the Need for Global Competition.